2002
DOI: 10.3402/meo.v7i.4543
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring for the New Millennium

Abstract: Abstract:The challenges and benefits of a formal mentoring program are considered within the context of learning organizations: specifically, graduate medical education and professional development. While no single definition addresses every aspect of mentoring, this process is a distinct one with established traditions and expectations. The core requirements of attraction, action and affect remain and are essential for this adult developmental process to be successful. This paper's review of the literature su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 17 publications
(24 reference statements)
4
41
0
Order By: Relevance
“…The qualities of the mentor reported by the participants in the present study are not unique and are comparable to those reported across the mentoring literature (23,33) . The important quality to note of the mentor in this study is the ability to facilitate group learning through an equal relationship.…”
Section: Safe and Supportive Learning Environmentsupporting
confidence: 86%
See 1 more Smart Citation
“…The qualities of the mentor reported by the participants in the present study are not unique and are comparable to those reported across the mentoring literature (23,33) . The important quality to note of the mentor in this study is the ability to facilitate group learning through an equal relationship.…”
Section: Safe and Supportive Learning Environmentsupporting
confidence: 86%
“…Effective mentoring relationships must have attraction (inspiration), action (investment) and affect (support) (33) . These data provide evidence of elements of these phases and components; however, they also demonstrate that mentoring relationships are not exact or linear and cannot be construed for professional development purposes.…”
Section: Safe and Supportive Learning Environmentmentioning
confidence: 99%
“…Formality, training of mentors and organisational support are significant factors identified as important for success in mentoring relationships (13) . The present study suggests that while formalised, clearly articulated outcomes for the mentoring partnership are important, informal mentoring relationships can develop competence.…”
Section: Characteristics Of the Mentoring Relationshipmentioning
confidence: 99%
“…1,2 Mentors' perceptions, attitudes and actions in modelling professionalism and improving the quality of patient care are important to the success of such structured mentorship programs, 3,4 despite the difficulty in applying metrics to the concept of mentorship. 5 However, mentoring successfully in the immediate aftermath of a conflict situation poses additional challenges that have infrequently been described.…”
mentioning
confidence: 99%